Affective Battlefields: Royal Gender Hybridity and the Cultural Afterlife of Friedrich II. (7th November 2018) - Maurer, Kathrin
Abstract: This article engages with a case of royal 'gender trouble', namely, the representation of Friedrich II in a popular history book: Franz Kugler and Adolph Menzel's History of Frederick the Great (1842). The article offers a brief overview of the political instrumentalisation of Friedrich II's body, and then engages with the representation of 'affective battlefields.' The analysis shows how these 'affective battlefields' become a stage on which writers and artists could display Friedrich's hybrid gendering. This hybridisation is finally discussed with reference to the book's political agenda, and, more broadly, representations of war, kings and power during the long eighteenth century.